O dissídio coletivo enquanto processo jurisdicional de formação na norma trabalhista: a emenda constitucional n.45/2004 e a violação do princípio da inafastabilidade da jurisdição - Pandolfi Neto, José (2010)
This study deals with the Labor Justice s Normative Power, as a jurisdictional process of norm formation. The objective is to question the directions traced by the Constitutional Amendment n. 45/2004, which disfigured its nature and imposed obstacles to the access to justice in the cases of economic collective disagreements dissidios. Firstly, it traces a panorama of conflict solution alternatives, as well as the dogmatic structure of this procedure model to demonstrate its importance in the context of the General Theory of the Process. From a new hermeneutic agenda and using an updated and multidisciplinary bibliography, the study questions the content of the referred amendment and it defends that its content goes against a number of Procedural Constitutional Principles, especially the principle of Jurisdiction Inafastabilit. As it is usual in an academic study, it presents the empirical and analytical evidence produced by Critical Social Theory studies, to demonstrate that the cited constitutional amendment was presented in a moment when the world is living a systemic crisis, caused by ultraliberal geopolitics, with deep implications in the world of labor; the recognized crises of contemporary unions and their negative impact in collective negotiations and strikes. It also suggests that its adoption is connected with the proposals disseminated by neocorporativism, which insists in the aversion of the State from the resolutions of these same conflicts and, in particular, it prevents the Labor Justice from exercising this normative power. Based on such arguments, the study concludes by defending the Normative Power and it proposes the recognition of the unconstitutionality of the referred constitutional amendment